Urbanism and empire in Roman Sicily - Pfuntner, Laura (Austin : University of Texas Press, 2019)
Sicily has been the fulcrum of the Mediterranean throughout history. The island?s central geographical position and its status as ancient Rome?s first overseas province make it key to understanding the development of the Roman Empire. Yet Sicily?s crucial role in the empire has been largely overlooked by scholars of classical antiquity, apart from a small number of specialists in its archaeology and material culture. Urbanism and Empire in Roman Sicily offers the first comprehensive English-language overview of the history and archaeology of Roman Sicily since R. J. A. Wilson?s Sicily under the Roman Empire (1990). Laura Pfuntner traces the development of cities and settlement networks in Sicily in order to understand the island?s political, economic, social, and cultural role in Rome?s evolving Mediterranean hegemony. She identifies and examines three main processes traceable in the archaeological record of settlement in Roman Sicily: urban disintegration, urban adaptation, and the development of alternatives to urban settlement. By expanding the scope of research on Roman Sicily beyond the bounds of the island itself, through comparative analysis of the settlement landscapes of Greece and southern Italy, and by utilizing exciting evidence from recent excavations and surveys, Pfuntner establishes a new empirical foundation for research on Roman Sicily and demonstrates the necessity of including Sicily in broader historical and archaeological studies of the Roman Empire.
Urban abandonment in the late Republic and early Principate (CA. 50 BC-AD 50) -- Urban abandonment in the high Empire (CA. AD 50-250) -- The southwestern coast : economic integration, political privilege, and urban survival -- The northeastern coast : civil war and colonization -- Eastern Sicily : from Syracusan to Roman hegemony -- Roman urbanism in Sicily -- New forms of settlement in Roman imperial Sicily.
Includes bibliographical references and index.
Description based on print version record.
eBooks on EBSCOhost
Keywords: Urbanization -- Italy -- Sicily -- History; Cities and towns -- Italy -- Sicily -- History; Sicily (Italy) -- Antiquities; Sicily (Italy) -- History -- To 800.; Rome -- Territorial expansion; Urbanisation -- Italie -- Sicile -- Histoire; Sicile (Italie) -- Histoire -- Jusqu'à 800.; Villes -- Italie -- Sicile -- Histoire; HISTORY -- Ancient -- Rome; HISTORY / Ancient / Rome; Antiquities; Cities and towns; Territorial expansion; Urbanization; Italy -- Sicily; Rome (Empire); To 800; Electronic books; History